The Ability of Student Math Literation on Problem Based Learning Model - Heka M. Tabun; Prida N. L. Taneo; Farida Daniel (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2020)
Students’ ability to mathematical literacy is very important in their math learning process. Less ability of mathematical literacy as students’ way of thinking, argumentation, and creating is no improvement so they face difficulties in solving math problems in their learning process related to real life. The analysis of the result from students of SMP Kristen 1 Mollo Selatan shows that they are still a low inability of mathematical literacy. The effect is questions that used as the exercise are common questions and not related to real life. To solve this problem, the researcher implemented Problem Based Learning (PBL) as a teaching literacy to improve students’ mathematical literacy abilities. This study will compare two classes in which one of them treated with PBL one of the other ones was not treated with PBL. A quasi-experiment quantitative method that used in this study with nonequivalent control group design. Two classes were selected as the sample by using simple random sampling. An essay test related to students’ mathematical literacy ability was used as the instrument to collect the data. The analysis technique in this study was an independent sample t-test to the result showed that the class which was treated used the PBL method was better than the class which was not treated used the PBL method. Students’ mathematical literacy ability in the PBL class was significantly proved in the high category with the score gain 0,8